Regarding mismatch between physical weight and the weight declared in the packing list and sticker mark on the material packs of ongoing shipment - Brac University (Brac University, 2023)
This record consists of general correspondence regarding mismatch between physical weight and the weight declared in the packing list and sticker mark on the material packs of ongoing shipment of BRACU new campus project.